Libyan Patient's Awareness and Attitude Towards Dental Implants - Abdulmutalib Rahab; Mohammed Abugufa; Khaled Alayan (International Journal of Medical Arts, 2023)
Background: There are many options to replace missing teeth, but a lot of people choose dental implants. It is important to know if patients know about dental implants in order to plan healthcare and marketing services.Aim of the work: To assess how much Libyan patients know about using implants as a way to replace a missing tooth, we also wanted to know what information they had about replacing missing teeth in general and where they learned it from.    Patients and Methods: A questionnaire survey was conducted to collect information from 400 people who went to different dental clinics and hospitals in Libya. We gathered information about the patients' traits, their knowledge on using implants for missing teeth, and where they found out about other ways to replace teeth.Results: Out of 500 patients, 400 patients said "yes" to joining this study.  A high percentage [80.2%] were aware of dental implants, with dentists being the primary source of information. The main barriers to considering implants were cost [78.8%] and perceived treatment time [19.8%]. Participants had varying estimations of the functional lifespan of implants, with the majority [37.5%] estimating it to be less than 10 years. A majority [80.2%] indicated their willingness to proceed with restoring missing teeth using dental implants. Almost half of the participants had heard about successful implant experiences from their friends. Participants had diverse views on the importance of functional outcomes and the qualifications of dentists providing implant treatment.Conclusion: A lot of patients feel that dental implants are expensive, so insurance companies and health authorities should find ways to make them more affordable. Dentists are very important as they help with replacing missing teeth by educating patients about dental implants and explaining why they are good options.